Exploring the Integration of Augmented Reality in Programming Education to Enhance Student Engagement in High Schools - Sharmar, Rahul; Patel, Priya (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
The integration of Augmented Reality (AR) in programming education has emerged as a promising approach to enhance student engagement and learning outcomes, particularly in high school settings. This study investigates the effectiveness of AR-based learning tools in improving students' understanding of programming concepts and fostering critical thinking skills. Using a mixed-methods approach, the research involved 60 high school students divided into an experimental group (using AR tools) and a control group (following traditional methods). Data was collected through surveys, classroom observations, performance assessments, and qualitative interviews. Results indicate that the experimental group demonstrated significantly higher levels of engagement, with 85% reporting increased interest in programming compared to 60% in the control group. Additionally, the experimental group outperformed the control group in both theoretical knowledge and practical application, scoring 25% higher on quizzes and completing tasks 20% faster. Qualitative feedback highlighted the immersive and interactive nature of AR as key factors in enhancing learning experiences. However, challenges such as technical difficulties and the need for teacher training were also identified. The findings suggest that AR can effectively bridge the gap between theoretical knowledge and practical application, making it a valuable tool for programming education. This study provides insights for educators and policymakers on integrating AR into curricula and highlights the importance of addressing technical and training barriers to ensure successful implementation.